1998
DOI: 10.4269/ajtmh.1998.59.66
|View full text |Cite
|
Sign up to set email alerts
|

Localization of eosinophil granule major basic protein in paracoccidioidomycosis lesions.

Abstract: Abstract. Paracoccidioidomycosis is a chronic granulomatous disease caused by the fungus Paracoccidioides brasiliensis. Although eosinophils have long been associated with the immune defense against helminths, the role of eosinophils in the immune response to fungal diseases is not as well studied. The eosinophil granule major basic protein is toxic to helminths and mammalian cells in vitro, and its release has been used as a marker of eosinophil localization and degranulation. To determine whether eosinophil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
2
18
0
4
Order By: Relevance
“…Similar findings have been described for coccidioidomycosis in which peripheral eosinophilia and eosinophilic microabscesses are correlated with progressive infection, indicative of a poor prognosis [5961]. Additional studies support the hypothesis that the eosinophil participates in the pathophysiology of PCM through its toxic granule proteins [6264]. In 2013, Muniz et al [65] stated that the cytoplasmic granules of eosinophils are able to function as “cluster bombs” amplifying the differential secretory properties of these cells, releasing cationic proteins, cytokines, chemokines, and growth factors which could contribute to the persistence of infection, exacerbation of the inflammatory response, and subsequent death of P. brasiliensis -infected neutrophil-depleted mice observed in the present study.…”
Section: Discussionsupporting
confidence: 74%
“…Similar findings have been described for coccidioidomycosis in which peripheral eosinophilia and eosinophilic microabscesses are correlated with progressive infection, indicative of a poor prognosis [5961]. Additional studies support the hypothesis that the eosinophil participates in the pathophysiology of PCM through its toxic granule proteins [6264]. In 2013, Muniz et al [65] stated that the cytoplasmic granules of eosinophils are able to function as “cluster bombs” amplifying the differential secretory properties of these cells, releasing cationic proteins, cytokines, chemokines, and growth factors which could contribute to the persistence of infection, exacerbation of the inflammatory response, and subsequent death of P. brasiliensis -infected neutrophil-depleted mice observed in the present study.…”
Section: Discussionsupporting
confidence: 74%
“…16 Although the role of eosinophils in the immune response to fungal infections has not been extensively studied, there are some results suggesting that Coccidioidomycosis, caused by the fungus Coccidioides immitis, may be accompanied by an increase in peripheral blood eosinophils of the order of 3-10%. 17 Moreover, during Paracoccidioidomycosis in humans, Wagner et al 18 have shown a clear association among the presence of Paracoccidioides brasiliensis, infiltration of the lesion by eosinophils and deposition of myelin basic protein (MBP) on the fungus. In this regard, Feldmesser et al 19 have demonstrated in vitro that rat eosinophils phagocytose opsonized C. neoformans yeasts, and they also observed a direct interaction between eosinophils and C. neoformans in vivo during an experimental murine intratracheal infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wagner et al [47] described in human samples that eosinophils were observed in direct association to or nearby P. brasiliensis. Nonetheless, in the majority of the corresponding publications, these cells were ignored, something that could be attributed to the fact that the haematoxylin and eosin stain often fails to show the presence of these cells [47]. In our model, we used special stainings such as Sirius Red to determine the presence of eosinophils (Fig.…”
Section: Inflammatory Cellsmentioning
confidence: 99%